2018
DOI: 10.1107/s205225251800711x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a practical implementation of X-ray ghost imaging with synchrotron light

Abstract: A practical experimental procedure for transmission X-ray ghost imaging (XGI) using synchrotron light is presented. The authors demonstrate the method, discuss data acquisition and analysis, and measure the point-spread function of an XGI system. The generalization of the methods for future experiments is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 51 publications
2
61
0
Order By: Relevance
“…Can multiplex sensing enable one to obtain more information for a given radiation dose? Many atomic resolution imaging tasks are radiation-damage limited, and the possibility to use multiplex sensing to overcome that limit has been discussed in recent literature [3][4][5]7]. This discussion has revolved around ghost imaging setups, where it has been suggested that damage might be avoided by decreasing the flux on the object branch and increasing the flux into the reference branch.…”
Section: Signal-to-noise Per Dosementioning
confidence: 99%
See 1 more Smart Citation
“…Can multiplex sensing enable one to obtain more information for a given radiation dose? Many atomic resolution imaging tasks are radiation-damage limited, and the possibility to use multiplex sensing to overcome that limit has been discussed in recent literature [3][4][5]7]. This discussion has revolved around ghost imaging setups, where it has been suggested that damage might be avoided by decreasing the flux on the object branch and increasing the flux into the reference branch.…”
Section: Signal-to-noise Per Dosementioning
confidence: 99%
“…There has been recent interest in the use of multiplex sensing techniques in applications at the atomic scale [1][2][3][4][5][6][7][8]. Traditionally, measurements using x-rays or electrons systematically interrogate a system at a single point in space, time, or photon/electron energy at once before moving on to the next measurement.…”
Section: Introductionmentioning
confidence: 99%
“…A generic schematic for X-ray ghost imaging in two spatial dimensions, (i.e., X-ray transform of the volume or projection images of the object), is shown in Fig. 1 [11], [12], [13], [14].…”
Section: Data and Illumination Patternsmentioning
confidence: 99%
“…The method has two key features. Firstly, the only photons (or other imaging quanta such as X-rays [10], [11], [12], [13], [14], atoms [15] etc.) that are registered by a positionsensitive detector are those that have never passed through the object.…”
Section: Introductionmentioning
confidence: 99%
“…The point-spread function (PSF) of our x-ray ghost-tomography experiment was calculated as the normalized auto-covariance of the ensemble of illuminating spatially random fields ( Fig. 2C) (11,12) . This PSF has a full-width at half-maximum (FWHM) of 98μm.…”
Section: S21 Motion Blurmentioning
confidence: 99%